IMPORTANCE OF LANGUAGE IN PUBLIC HEALTH SERVICES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
Language is a key tool for healthcare doctors to manage consultation and any type of communication along with clients. Many think that being a good doctor means having enough knowledge on medicine however it is not only about clinical skills, it can be also language skill performance, providing clear and accurate dialogue with patients.